On the correct lectotype for Marmessoidea unicolor Redtenbacher, 1908 (Insecta: Phasmatodea) - Seow-Choen, Francis; Ng, Peter K. L. (Zootaxa, 2023)
Hennemann, F.H., Conle, O.V. & Brock, P.D. (2023) The types of Phasmatodea (= Phasmida) deposited in the Eidgenössisches Technisches Hochschulzentrum, Zürich, Switzerland (ETHZ). Zootaxa, 5278 (1), 176–188. https://doi.org/10.11646/zootaxa.5278.1.10 Hovinga, H. (2010) The Sumatra Railroad: Final destination Pakan Baroe, 1943–1945. Brill, Leiden, 391 pp. https://doi.org/10.1163/9789004253711 ICZN [International Commission on Zoological Nomenclature] (1999) International Code of Zoological Nomenclature. International Commission of Zoological Nomenclature. 4th Edition. Adopted by the XXI General Assembly of the International Union of Biological Sciences. International Trust for Zoological Nomenclature, in association with the British Museum (Natural History), London, 338 pp. Redtenbacher, J. (1908) Die Insektenfamilie der Phasmiden. III. Phasmidae Anareolatae (Phibalosomini, Acrophyllini, Necrosciini). Wilhelm Engelmann, Leipzig, pp. 341–589, pls. 16–27. Seow-Choen, F. (2021) A Taxonomic Guide to Stick Insects of Peninsular Malaysia. Vol. 1. Natural History Publications, Borneo, Kota Kinabalu, 944 pp. Weidmann, W. (1936) ‘Der Schweizer als Pionier und Kolonist in Sumatra’. In: Der Schweizer Verein Deli-Sumatra (Ed.), Der Schweizer Verein Deli-Sumatra: Zum fünfzigjährigen Bestehen, 1886–1936. Buchdruckerei der Neuen Zürcher Zeitung, Zürich, pp. 33–48.